Protection and profit: Empirical evidence of governmental and market-based forest policies - Julika Herzberg (Philipps-University Marburg, School of Business and Economics, 2019)
In this paper, I study the effectiveness of privately managed FSC certified forests and public sustainability reserves distributed over the entire Brazilian Amazon from 2002-2015. The paper uses high-resolution data on forest cover derived from satellite images and organized in a grid of 1 km2 cells. Using a difference-in-differences estimator in a regression discontinuity environment, I find an increase in deforestation of an annual area of 8,057 ha in FSC forests after the certification. Public sustainability zones' impact on deforestation is also positive but declines over time. The effectiveness of both type of zones improves if they are located closer to (export) markets or existing infrastructure.
Keywords: J43; O13; O14; Q15; Q17; 330; deforestation; commodity prices; sustainable forest management